IMPLEMENTASI METODE SMART LEARNING SOLUTION BERDASAR TEORI MULTIPLE INTELIGENCE DALAM PENGEMBANGAN POTENSI ANAK USIA DINI - Violinda, Qristin (Indonesian Journal of Early Childhood Education Studies, 2012)
The purpose of this research is to produce a smart method of learning a conduciveÂ  learning solution in order to develop multiple intelligences in early childhood students in Semarang. The approach taken is descriptive qualitative research. The findings of this study, that the smart method of learning the model-based learning solution to maximize the potential of multiple Intelligence itself is effective in early childhood. Multiple intelligences include spatial, linguistic, interpersonal, musical, natural, body / KINESTHETIC, intrapersonal, and logical-mathematical. This study is also effective to improve teacher performance, so it can be said to be smart method of learning is an effective solution to improve the quality of learning.